The kindness of the queen - Saniyasnain, Khan (New Delhi : Goodword Books, 2009)
This series will help children appreciate the best loved stories from the Quran, which will become a foundation for them for further reading. As a pre-school reading course, it will help parents to explain and enrich the divine message by a simple and easy to understand method.